KEKERASAN TERHADAP PEREMPUAN DALAM RUMAH TANGGA (KAJIAN DARI PERSPEKTIF HUKUM DAN GENDER) - Sukerti, Ni Nyoman (Jurnal Studi Jender SRIKANDI; Vol. 6, No. 2 Juli 2007)
iolence against women is not only as an individual issue but also as a local, anational and global issue. It is said that global issue can be seen by regulating international law such Wiena Declaration, Convention on the Elimination of All Forms Discrimination Against Woman (1979) Declaration of Violence Against Woman (1993), and Bejing Declaration and Platform for Action (1995). Nationally, the law regulation about issue can be seen in as Criminal Law, Private Law, Act Number 1, 1974, Act Number 7, 1984, Act Number 39, 1999, and Act Number 23, 2004. Although protection against women has been regulated nationally and internationally, in the several states that mention above but in relity violence against woman still exists and increase from year. From back ground that above a problem arises as polows: What is the factors of violence against woman in a household and What is the protection obtained by woman as victim of violence in a household. The factors of violence: patriarchical etc and from of protection received by woman as victim of violence in ahousehold as Criminal Law, Private Law, Act Number 1, 1974, Act Number 7, 1984, Act Number 39, 1999, and Act Number 23, 2004.
Keywords: Violence, woman, household